Chitosan nanoparticle coatings reduce microbial growth on fresh‐cut apples while not affecting quality attributes. (16th July 2014) - Pilon, Lucimeire; Spricigo, Poliana C.; Miranda, Marcela; de Moura, Márcia R.; Assis, Odilio Benedito G.; Mattoso, Luiz Henrique C.; Ferreira, Marcos David
Abstract This study addressed the effects of chitosan‐based nanoparticles on microbiological quality, colour, polyphenol oxidase (PPO) and peroxidase (POD) and firmness of fresh‐cut 'Gala' apple slices during storage at 5 °C for 10 days. The treatments carried out were as follows: (i) slices pulverised with 110‐nm chitosan nanoparticles, (ii) slices pulverised with 300‐nm chitosan nanoparticles, (iii) 2 g L−1 chitosan dissolved in 2% citric acid and (iv) noncoated samples. There was an increase in chroma and a proportional decrease in hue angle and lightness. Browning of the slices coated with conventional chitosan and control was slightly intense than those coated with chitosan nanoparticles of 110 and 300 nm. The PPO and PDO activities increased with time for all samples, with irrelevant difference among the treatments. Flesh firmness did not change for any treatment and period. Coatings with chitosan nanoparticles of 110 nm showed higher antimicrobial activity against moulds and yeasts, and mesophilic and psychrotrophic bacteria than the other treatments. No Salmonella, and total and faecal coliforms were detected. This investigation supports the potential use of chitosan nanoparticles as edible coatings in controlling microbial activity in fresh‐cut apples.